Diseño de dispositivo que permita a los motociclistas generar una personalización en los elementos de protección personal incentivando así su compra y uso (2021)
This project presents the design process of an accessory system that allows motorcyclists to personalize personal protection elements for the lower limbs (knee pads), because it presents the opportunity to impact a field that has had an exponential growth in the country over the years such as the motorcycle sector, which in turn has the largest number of affected within the figures of road accidents in Colombia presented by the national road safety agency and the national road safety observatory.